2022
DOI: 10.3390/ijerph20010590
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Family Functionality in Prosocial Behaviour and School Climate in Adolescence

Abstract: Adolescence entails a series of changes in young people who need to adopt socially positive behaviours and have a beneficial family and school environment. The main objective of this research is to analyse the relationships established between the variables of prosocial behaviour and school climate, as well as to check whether family functionality plays a moderating role in this relationship. The participants were a total of 743 adolescent students between 14 and 19 years of age from different schools in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…As documented in previous studies, e.g., [16,36], better functioning in the family environment has an impact on adolescents' psychological well-being. Previous research has also demonstrated associations between emotional intelligence and emotional functioning [8,13,19], as well as positive relationships between psychological well-being and emotional intelligence [26,34]. Based on this knowledge, we proposed our first hypothesis and obtained in the results the existence of a positive correlation between family functioning and all dimensions of the Psychological Well-Being scale, as well as a positive correlation between family functioning and emotional intelligence, and between most dimensions of psychological well-being and emotional intelligence, except for emotional attention, which does not correlate with self-acceptance or positive relationships with others and correlates negatively with autonomy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As documented in previous studies, e.g., [16,36], better functioning in the family environment has an impact on adolescents' psychological well-being. Previous research has also demonstrated associations between emotional intelligence and emotional functioning [8,13,19], as well as positive relationships between psychological well-being and emotional intelligence [26,34]. Based on this knowledge, we proposed our first hypothesis and obtained in the results the existence of a positive correlation between family functioning and all dimensions of the Psychological Well-Being scale, as well as a positive correlation between family functioning and emotional intelligence, and between most dimensions of psychological well-being and emotional intelligence, except for emotional attention, which does not correlate with self-acceptance or positive relationships with others and correlates negatively with autonomy.…”
Section: Discussionmentioning
confidence: 95%
“…It has been documented that functionality at the family level that promotes these coping and adaptation skills in adolescents, together with higher levels of life satisfaction, has an impact on a greater state of psychological well-being [19]. Psychological well-being can be conceptualised from a eudaemonic perspective that refers to the active process that an individual carries out that is characterised by the pursuit and achievement of personal goals and the experience of engaging in life activities, thus allowing for a broader understanding of well-being given the relevance of these aspects to a full and satisfying life [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of females themselves, compared to single participants, females in a stable relationship exhibit decreased attention to opposite gender interaction partners and increased attention to same gender interaction partners ( Karremans and Verwijmeren, 2008 ). Previous studies have shown that compared to males, females tend to exhibit higher levels of empathy and respect, indicating that their level of empathy may be higher ( González Moreno and Molero Jurado, 2022 ). Furthermore, in another study using hyperscanning, the findings revealed that stronger mutual attention during social interactions leads to enhanced interbrain synchronization among participants, thereby facilitating their ability to engage in specific interactions and better achieve goals ( Gvirts and Perlmutter, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching practices have not changed much over the years, so classroom activities are not geared towards fostering creative thinking skills [15,16]. It is worth highlighting the importance of fostering a positive school climate to enhance adolescents' personal well-being [17].…”
Section: Introductionmentioning
confidence: 99%